Trans‐specific evolution of opsin alleles and the maintenance of trichromatic colour vision in Callitrichine primates - Alison K. Surridge; Nicholas I. Mundy (Molecular Ecology, 2002)
Many New World (NW) primates possess a remarkable polymorphism in an X‐linked locus, which encodes for the visual pigments (opsins) used for colour vision. Females that are heterozygous for opsin alleles of different spectral sensitivity at this locus have trichromatic colour vision, whereas homozygous females and males are dichromatic, with poor colour discrimination in the red–green range. Here we describe an extensive survey of allelic variation in both exons and introns at this locus within and among species of the Callitrichines (marmosets and tamarins). All five genera of Callitrichines have the X‐linked polymorphism, and only the three functional allelic classes described previously (with maximum wavelength sensitivities at about 543 nm, 556 nm and 563 nm) were found among the 16 species and 233 or more X‐chromosomes sampled. In spite of the homogenizing effects of gene conversion, phylogenetic analyses provide direct evidence for trans ‐specific evolution of alleles over time periods of at least 5–6 million years, and up to 14 million years (estimated from independent phylogenies). These conclusions are supported by the distribution of insertions and deletions in introns. The maintenance of polymorphism over these time periods requires an adaptive explanation, which must involve a heterozygote advantage for trichromats. The lack of detection of alleles that are recombinant for spectral sensitivity suggests that such alleles are suboptimal. The two main hypotheses for the selective advantage of trichromacy in primates are frugivory for ripe fruits and folivory for young leaves. The latter can be discounted in Callitrichines, as they are not folivorous.